Penentuan SPF Lip Balm Tabir Surya Berbasis Ekstrak Wortel Menggunakan Metode Spektrofotometri UV-Vis: SPF Determination of Carrot Extract-Based Sunscreen Lip Balm Using UV-Vis Spectrophotometry Method - Hilmia Lukman; Vivi Shofia; Aidlatul Latifah; Nadira Nadira (JURNAL FARMASI DAN MAKANAN, 2025)
Lips are highly vulnerable to ultraviolet (UV) radiation due to the absence of natural protective structures such as hair follicles and sweat glands. Excessive UV exposure may lead to dryness, irritation, cracking, and premature aging. This study aimed to evaluate the Sun Protection Factor (SPF) of carrot (Daucus carota L.) root extract and lip balm formulations containing the extract. Carrot roots were extracted using the reflux method with 96% ethanol. Lip balm formulations were prepared using varying concentrations of carrot extract: 0%, 10%, 15%, and 20%. SPF values were determined in vitro using UV-Vis spectrophotometry at wavelengths of 290–320 nm. Results showed that SPF values increased with extract concentration, from 8.65 at 500 ppm to 18.78 at 2000 ppm, classified as maximum to ultra protection. Among the lip balm formulations, the highest SPF was obtained from formula F3 (20% extract) with an SPF of 5.35, categorized as moderate protection. The photoprotective effect is attributed to β-carotene and flavonoids in carrot extract, which act as antioxidants and UV absorbers. These findings suggest that carrot root extract has promising potential as a natural active ingredient in sunscreen formulations, particularly for lip care products.